Sporotrichal arthritis. Issue 2 (February 1991) - Chowdhary, G; Weinstein, A; Klein, R; Mascarenhas, B R
Abstract : Sporotrichal arthritis is a rare disease entity. Diagnosis is often difficult and delayed. Presentation may be either monoarticular or polyarticular. A case of polyarticular sporotrichal arthritis which exemplifies these problems is reported.